Fiber Orientation Tensors and Mean Field Homogenization Application to Sheet Molding Compound - Bauer, Julian Karl (Schriftenreihe Kontinuumsmechanik im Maschinenbau, 2023)
Effective mechanical properties of fiber-reinforced composites strongly depend on the microstructure, including the fibers' orientation. Studying this dependency, we identify the variety of fiber orientation tensors up to fourth-order using irreducible tensors and material symmetry. The case of planar fiber orientation tensors, relevant for sheet molding compound, is presented completely. Consequences for the reconstruction of fiber distributions and mean field homogenization are presented.